DG Placement Using Loss Sensitivity Factor Method for Loss Reduction and Reliability Improvement in Distribution System - Sasi Kumar, G.; S.Sarat Kumar, Dr.; S.V.Jayaram Kumar, Dr. (International Journal of Engineering and Technology, 2018)
The electrical power distribution system is designed to provide a reliable electrical supply to its consumers as economically as possible. The key factor in any electrical power system is the power loss due to resistance during transmission and distribution. However the power loss in the distribution network is more than in the transmission  network because of high R/X ratio. To minimize these losses in the distribution system, now a days, Distribution Generators (DG’s) are introduced in the network. The addition of DG’s in the radial distribution system provides many technical and cost benefits to both utilities and customers. However, improper placement of these DG’s may cause negative impacts on the overall system performance. Hence an optimum location of DG’s in the radial distribution system plays vital role.In this paper, an analytical method to calculate optimal size and to identify optimal location of DG’s is considered to minimize the power losses and to improve voltage profile and Reliability in distribution systems. The methodology is applied to IEEE 33-bus Radial Distribution System and the obtained results are compared.
Keywords: Distribution Generation; Loss sensitivity Factor; Reliability Indices; Radial Distribution System.